Joseph R. Wiebe, The Place of Imagination: Wendell Berry and the Poetics of Community, Affection, and Identity. (19th September 2019) - Baker, Jack
Abstract : Joseph R. Wiebe, The Place of Imagination: Wendell Berry and the Poetics of Community, Affection, and Identity (Waco, TX: Baylor University Press, 2017), 272 pp., 49.95 (cloth), ISBN: 978-1-481-30386-6.